2018
DOI: 10.1149/2.1301811jes
|View full text |Cite
|
Sign up to set email alerts
|

NiFe-Layered Double Hydroxide Sheets as an Efficient Electrochemical Biosensing Platform

Abstract: The maximum allowed limits of chlorpromazine (CPZ) established by Food and Drug Administration (FDA) for children aged between 1 and 5 years is 0.125 mM and between 6 to 12 years is 0.235 mM. However, excess consumption of CPZ beyond these permissible limit cause adverse health effects. In order to detect CPZ, herein, we employ NiFe-layered double hydroxide sheets modified glassy carbon electrode (GC/NiFe LDH). The GC/NiFe LDH electrode exhibited a good electrocatalytic activity towards CPZ detection at a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Tao et al reported the use of NiFe-LDH for sensing hydrogen peroxide, with a sensitivity of 1704 μA mM –1 cm –2 . Nesakumar et al explored the use of NiFe-LDH for chlorpromazine sensing . Lu et al reported the use of NiFe-LDH (3:1) in the electrochemical sensing of glucose molecules, but the oxygen evolution reaction (OER) contribution has not been discussed .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tao et al reported the use of NiFe-LDH for sensing hydrogen peroxide, with a sensitivity of 1704 μA mM –1 cm –2 . Nesakumar et al explored the use of NiFe-LDH for chlorpromazine sensing . Lu et al reported the use of NiFe-LDH (3:1) in the electrochemical sensing of glucose molecules, but the oxygen evolution reaction (OER) contribution has not been discussed .…”
Section: Introductionmentioning
confidence: 99%
“…17 Nesakumar et al explored the use of NiFe-LDH for chlorpromazine sensing. 20 Lu et al reported the use of NiFe-LDH (3:1) in the electrochemical sensing of glucose molecules, but the oxygen evolution reaction (OER) contribution has not been discussed. 18 In this class of materials, it is imperative to note that the onset potential for oxygen evolution and the glucose oxidation potential are close such that they might have an impact on glucose sensing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, metals and metal oxides have been extensively studied in the sensing fields, such as Pt, Au, Ni, Fe, Ag, ZnO, NiO, TiO 2 and Fe 2 O 3 . 21,22 Among them, ZnO and NiO have attracted extensive attention due to their environmental friendliness, high specific surface area and superior electrochemical properties. [23][24][25] The composite of NiO-ZnO, based on an incorporation of p-type semiconductor NiO and n-type semiconductor ZnO, combines the different properties of individual ingredient and enhance sensing performance through their cooperative effect.…”
mentioning
confidence: 99%
“…Layered double hydroxides (LDHs), a kind of extraordinary two-dimensional (2D)-layered nanomaterials, have obtained wide attention by virtue of their large charge density along prep the 2D backfin space height in application scenarios of photocatalysts, thermocatalysts, and electrocatalysts. Wang et al reported MoO 3 /Zn-Al LDHs composites as photocatalysts for photocatalytic elimination of tetracycline target pollutants . Ao et al reported that the MB target pollutant molecules can be completely eliminated using three-dimensional (3D) flower-like Ag 2 CO 3 /Mg-Al LDHs photocatalysts within 40 min under visible-light irradiation .…”
Section: Introductionmentioning
confidence: 99%